2015
DOI: 10.1136/archdischild-2015-308315
|View full text |Cite
|
Sign up to set email alerts
|

Delivery room end tidal CO2monitoring in preterm infants <32 weeks

Abstract: Delivery room EtCO2 monitoring is feasible and safe. EtCO2 values obtained after birth reflect the establishment of functional residual capacity and effective ventilation. The potential short-term and long-term consequences of EtCO2 monitoring should be established in randomised controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…In two studies, compromised neonates with bradycardia at birth who received mask resuscitation demonstrated an increase in exhaled carbon dioxide before their heart rates were restored and their preductal oxygen saturations increased . The long‐term value of capnography‐guided resuscitation is uncertain, as neither quantitative nor qualitative capnography has been shown to improve arterial carbon dioxide levels when compared to just clinical assessment . Capnography can monitor lung aeration in various clinical settings, including the NICU and during neonatal transport.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In two studies, compromised neonates with bradycardia at birth who received mask resuscitation demonstrated an increase in exhaled carbon dioxide before their heart rates were restored and their preductal oxygen saturations increased . The long‐term value of capnography‐guided resuscitation is uncertain, as neither quantitative nor qualitative capnography has been shown to improve arterial carbon dioxide levels when compared to just clinical assessment . Capnography can monitor lung aeration in various clinical settings, including the NICU and during neonatal transport.…”
Section: Resultsmentioning
confidence: 99%
“…10 Clinical studies on premature neonates at birth have also demonstrated a rise in carbon dioxide at delivery, correlated to an increase in tidal volume. [11][12][13] One study focused on premature neonates who had not established spontaneous ventilation and required positive pressure ventilation in the delivery room.…”
Section: Key Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] The feasibility and efficacy of exhaled CO 2 devices in establishing the adequacy of noninvasive ventilation either as face mask positive-pressure ventilation or in providing CPAP, both in clinical settings and in mannequin models, have been published. 5,8,9 Although not yet officially recommended due to lack of substantial outcome data, the ease and familiarity of using colorimetric devices make them excellent candidates for further research. 1,7 As the field investigates SEE THE ORIGINAL STUDY ON PAGE 1003 potentially prolonged use of these devices with noninvasive support, the article by Brown et al 10 in this issue of RESPIRATORY CARE brings attention to a key characteristic of exhaled CO 2 devices, namely their air flow resistance.…”
mentioning
confidence: 99%